Resisting the change to user stories: a trip to Abilene. (1st December 2005) - McAvoy, John; Butler, Tom
Agile software development projects embrace change, yet change is problematic in any software development project. Resistance to change is a common trait and software developers are not different than other organisational actors in this regard. The resistance to change is often inexplicable, even to those who are resisting. This paper describes a case study, which examines the changes to the IS development environment wrought by the introduction of a new software development methodology. One aspect of the new methodology involves the use of user stories in place of traditional requirements documentation. The findings of this longitudinal study illustrated that developers' commitment to the use of user stories diminished greatly, ranging from initial commitment to skepticism, to virtual abandonment. To explain the underlying reasons for the reduction in commitment, the authors used the theory of competing commitments. Competing commitments are typically subconscious forces that work against behaviours and actions that social actors were previously committed to. Further to the use of the competing commitment process, this paper's analysis of the software development project suggested the presence of the Abilene paradox influencing the diminishing commitment. Under the Abilene paradox, the actors themselves cannot adequately explain why the change is resisted. The use of competing commitments enabled the actors to discover themselves why the change is resisted.